(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
This article presents some kindergarten geometry activities that we can find in the education portal Application of Curriculum Resources (ARC). At this portal, teachers can share activities, resources and / or classroom materials, organized around the curriculum. In this paper, we present activities made by Isabel Sorigué, early childhood education teacher, ranging from handling materials to use the GeoGebra software in kindergarten.